Dragon curse - McMann, Lisa (McMann, Lisa. Unwanteds quests, 2019)
Back in Artimé, the three Stowe siblings' happy reunion is short-lived. Fifer loses her position, Thisbe grows determined to rescue the other black-eyed children, and Aaron faces opposition from Frieda Stubbs. Meanwhile, an attack by the Revinir puts all of Artimé at risk.